Assessments of quality of life in burn patients after hospital treatment in Jember - Agnellia Maulidya Utami; Ulfa Elfiah; Desie Dwi Wisudanti (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2020)
Background: Burn injuries can contribute to physical and psychological problems affecting quality of life (QoL). The QoL is a parameter to assess medical results after treatment. In Indonesia, studies concerning burn patients’ QoL after treatment are still limited.Objective: This study aims to observe correlations between 8 dimensions of QoL after treatment and histories of burn severity, numbers of surgical procedures, and lengths of hospital stayMethods: A cross sectional study was conducted in December 2018. Subject criteria of this study were patients who have experienced burn injuries for the last 2 years and have been treated at dr. Soebandi Hospital Jember. Then all the patients were discharged from the hospital by following medical advice in recovered conditions. They were asked to complete SF-36 questionnaires that consist of 8 dimensions of QoL. Every dimension was correlated with histories of burn severity, numbers of surgical procedure, and lengths of hospital stay. Next, the obtained data were analysed by Pearson and Spearman.Results: 13 subjects or patients were analysed. Most of them (38.5%) were adults in a range of 41 – 50 years old and were male (69.2%). A bivariate analysis found a significant negative correlation between burn severity and QoL in physical functions, bodily pains, and mental health dimensions (p=0.030, p=0.012, p=0.044). A significant negative correlation was also reported between numbers of surgical procedures and QoL in physical role dimensions (p=0.047). Lengths of hospital stay had a significant negative correlation with physical functions and physical role dimensions (p=0.044, p=0.031).Conclusion: This study revealed significant correlations between burn severity, numbers of surgical procedures, length of hospital stay and the various dimensions of QoL. This study also provided data of QoL, so in the future burn centres can identify dimensions of QoL after burn injuries and can improve their burn management and patient care to improve their QoL.